The room next door [videorecording (DVD)] - Almodóvar, Pedro; Moore, Julianne; Swinton, Tilda; Turturro, John, 1957-; Iglesias, Alberto; Grau, Eduard, 1981-; Nunez, Sigrid (Sony Pictures Classics, 2025)
Ingrid and Martha were close friends in their youth, when they worked together at the same magazine. Ingrid went on to become a novelist while Martha became a war reporter. Separated by the circumstances of life and after years of being out of touch, they meet again in an extreme but strangely sweet situation.